Modelo dialógico de convivência: o clube de valentes na formação de professores e professoras dos anos iniciais na educação básica - Gouveia, Jennifer Vila Nova (2025)
The present research aimed to analyze transformative and exclusionary elements in the implementation of the “Clube de Valentes,” considering bullying as the central form of violence to be overcome. The study sought to understand how this pedagogical practice, already implemented in schools in different countries, can contribute to the prevention and resolution of conflicts among students in the early years of basic education in Brazil, fostering a dialogical and collaborative school environment. A continuing education program was conducted with teachers from a school using a dialogical perspective, and the research employed the communicative methodology within a qualitative approach. Data collection methods included questionnaires, field journals, communicative reports, and communicative discussion groups with the teachers participating in the training, as well as with some children and families involved in the implementation of the “Clube de Valentes” by the teachers after receiving the training. Data collection procedures were carried out both in person and remotely. The results indicated that the intervention is effective, but only when integrated with other successful educational actions, rather than applied in isolation.